2019
DOI: 10.3389/fncom.2019.00081
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Preoperative Magnetic Resonance Imaging Reveals Transcriptomic Classification of de novo Glioblastoma Patients

Abstract: Glioblastoma, the most frequent primary malignant brain neoplasm, is genetically diverse and classified into four transcriptomic subtypes, i. e., classical, mesenchymal, proneural, and neural. Currently, detection of transcriptomic subtype is based on ex vivo analysis of tissue that does not capture the spatial tumor heterogeneity. In view of accumulative evidence of in vivo imaging signatures summarizing molecular features of cancer, this study seeks robust non-invasive radiographic markers of transcriptomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…AI can be used to differentiate between four molecular subtypes of glioblastoma: Neural, proneural, mesenchymal and classical by using the transcriptomic profiling tool (28). Research based on standard MRI sequences that used SVM obtained an accuracy of 71% in distinguishing the four subtypes (29).…”
Section: Resultsmentioning
confidence: 99%
“…AI can be used to differentiate between four molecular subtypes of glioblastoma: Neural, proneural, mesenchymal and classical by using the transcriptomic profiling tool (28). Research based on standard MRI sequences that used SVM obtained an accuracy of 71% in distinguishing the four subtypes (29).…”
Section: Resultsmentioning
confidence: 99%
“…One more limitation of our study is that we used retrospective multi-institutional data; a prospective dataset comparing our methods to standard histopathological review would lend further validity and confidence to our ML models. Future work would include the creation and validation of ML models through the neuro-CaPTk application for various other molecular characterizations, including transcriptomic subtypes, 50 as well as detection of other distinct molecular markers (eg, PTEN, TP53, and ATRX). Moreover, enthusiastically taking on the evolving field of integrated diagnostics, we aim to provide comprehensive diagnostic modules integrating radiology, pathology, and clinical markers in neuro-CaPTk.…”
Section: Discussionmentioning
confidence: 99%
“…It identifies the tumors into four molecular subtypes; classical, mesenchymal, proneural, and neural [ 27 ]. A study that applied SVM and based on conventional MRI sequences showed 71% accuracy in delineating the four subtypes [ 60 ].…”
Section: Radiomics Of Gliomasmentioning
confidence: 99%